A systemic approach to West African migratory movements - (:unkn) unknown (My University, 2021)
The research is part of a scientific and sociological approach aimed at revealing the main factor pushing a West African national to leave his or her country and at analyzing its interactions with other migratory determinants. An examination in time and space of voluntary or forced population movements in the sub-region shows that West African mobility is undergoing deep changes and that it has a major impact on extra-regional countries, particularly the European Union member states. A presentation of migration theories highlights that the analysis of migratory flows can only be carried out within a multidisciplinary and cross-cutting framework. A field survey of 18 interviews, additional data, and its examination reveal that the predominant factor triggering the migration process is economic. Starting from this factor, a careful analysis of its interaction with the other factors established during the survey underlines that the "environment" influences the main factor triggering migration. A detailed examination of the main determinants then allows the modeling of the decision-making process specific to West African migration in the form of an influence graph. This action highlights the importance of three underlying dynamics relating to sources of information, economic insecurity, and the relationship between the state and smuggling of migrants, of which the state represents the single common point, making it a pivot in the decision-making process.
Keywords: African Research